2018
DOI: 10.3847/1538-4357/aaef86
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Loops above a Small Flux-emerging Region Observed by IRIS, Hinode, and SDO

Abstract: I report on observations of a set of magnetic loops above a region with late-phase flux emergence taken by IRIS, Hinode and SDO. The loop system consists of many transition region loop threads with size of 5-12 ′′ in length and ∼ 0.5 ′′ in width and coronal loops with similar length and ∼ 2 ′′ width. Although the loop system consists of threads with different temperatures, most individual loop thread have temperature in a narrow range. In the middle of the loop system, it shows clear systematic blue-shifts of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 86 publications
1
12
0
Order By: Relevance
“…Densities obtained here for cool loop is quite higher than those reported by Huang et al (2015) of about 10 10 cm −3 at transition region temperature. However, densities are comparable with findings of Huang (2018) for a cool loop reaching temperature up to 2 MK. For hot loop, Gupta et al (2018) found electron densities to be 10 11.5 cm −3 for transition region temperature whereas Testa & Reale (2020) found densities reaching of the order of 10 10 cm −3 at hot coronal temperatures.…”
Section: Discussion and Summarysupporting
confidence: 85%
“…Densities obtained here for cool loop is quite higher than those reported by Huang et al (2015) of about 10 10 cm −3 at transition region temperature. However, densities are comparable with findings of Huang (2018) for a cool loop reaching temperature up to 2 MK. For hot loop, Gupta et al (2018) found electron densities to be 10 11.5 cm −3 for transition region temperature whereas Testa & Reale (2020) found densities reaching of the order of 10 10 cm −3 at hot coronal temperatures.…”
Section: Discussion and Summarysupporting
confidence: 85%
“…The interaction of small loops has been taken as explanation of a small flare observed with IRIS (Alissandrakis et al 2017), and our study provides direct evidence from the morphology observed in the hot AIA channels counterparts. Many recent papers have studied simultaneous observations from IRIS and SDO/AIA to investigate magnetic rearrangements causing localized brightenings in the transition region, and likely related with flux emergence (e.g., Jiang et al 2015;Toriumi et al 2017;Guglielmino et al 2018;Huang 2018;Tian et al 2018;Guglielmino et al 2019). However we note that the coronal heating events we study here have quite different properties with respect to those events, in that they have generally lower Doppler shift velocities (up to ∼ ±30 km/s) and show heating of the overlying coronal loops to several MK.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some coronal loops can be seen from the AIA 131 and 171 Å images in the same region. It is likely that cool and hot loops are mixed in this region [63,64,65].…”
Section: Spectral Characteristics Of Uv Burstsmentioning
confidence: 99%